Planetarium - Brenner, Barbara; Miller, Ron, 1947- (New York : Bantam Books, 1993)
Presents facts about each planet through a tour of a planetarium.
Includes index.
"A Byron Preiss book."
"A full color Planetarium wall poster inside"--Cover.
Keywords: Planetariums -- Juvenile literature; Outer space